Noninvasive Estimation of Pulmonary Vascular Resistance Using Right Ventricular Outflow Doppler Analysis - Luis Afonso, MD; Chandra Kanth Ala, MD; Aditya Sood, MD; Oluwole Adegbala, MD, MPH; Farima Kahe, MD; John Dawdy, MD; Kendall Bell, MD; Abdul Rasheed Bahar, MD; Nimrod Blank, MD (JACC: Advances)
Background: Right heart catheterization (RHC) is the gold standard for measuring pulmonary vascular resistance (PVR). Current noninvasive methods lack accuracy, especially in moderate to severe pulmonary arterial hypertension. Objectives: The objective of the study was to develop and validate a novel echocardiographic method for estimating PVR using right ventricular outflow tract Doppler notch analysis. Methods: In this prospective study, of 95 patients undergoing RHC, 35 with isolated postcapillary pulmonary hypertension (PVR <2.0 WU) and no discernible Doppler notches were excluded. Of the remaining, 54 patients with interpretable Dopplers were divided into derivation (n = 30) and validation (n = 24) cohorts, all undergoing invasive PVR (iPVR) measurement and echocardiography within 24 hours. Right ventricular outflow tract Doppler, specifically the ratio of notch time (NT) to ejection time, was analyzed to derive a regression equation for non-invasive PVR (niPVR). The model was validated against iPVR and compared with 5 existing methods. Results: Stepwise linear regression identified the inverse of NT as the strongest predictor of iPVR. After adjusting for heart rate, the model (R2 = 0.93) yielded non-iPVR = 7.1∗(ejection time/NT) − 9.36. Validation against 5 established methods showed superior performance across a PVR range of 2.3 to 14.2 WU, with the highest Pearson correlation (r: 0.76; P < 0.0001; 95% CI: 0.52-0.89). Bland-Altman analysis confirmed superior agreement. Conclusions: This novel echocardiographic method offers feasible, rapid, reliable PVR estimation with strong correlation to invasive measurements. Although not a substitute for RHC, this promising preliminary finding from a selective cohort may aid in identifying candidates for invasive testing and guide pulmonary hypertension management. Larger, multicenter validation is warranted.